Immunohistochemical Study of the Endocrine Cells in the Lung of the Ostrich (Struthio camelus) - Tarakci, Berrin Gencer; Yaman, Mine; Yaman, Ihsan; Bayrakdar, Ali; Parlak, Tuba (Medwell Online, 2008)
The presence of serotonin, calcitonin, somatostatin-14, cholecystokinin (CCK), calcitonin gene related peptide (CGRP) endocrine cells in the lung of the ostrich (Struthio camelus) was investigated by immunohistochemistry. CGRP and serotonin immunoreactivity were observed in the PNEC cell (pulmonary neuroendocrine cell) with intermediate and low frequencies, respectively. Somatostatin containing cells were scarcely observed. CCK and calcitonin were not detected. These results suggesting that CGRP, serotonin and somatostatin may be involved in the lung ontogeny.
Keywords: Pulmonary neuroendocrine cell; lung; ostrich; immunohistochemistry